The Implementation of the STEM PBL Approach for Students with Disabilities: A Literature Review - Wulandary, Verra; Kawai, Norimune (Universitas Pendidikan Indonesia (UPI), 2025)
The present systematic literature review (SLR) investigates the successes and challenges associated with the implementation of Project-Based Learning (PBL) grounded in the Science, Technology, Engineering, and Mathematics (STEM) framework for students with disabilities. The authors meticulously analyzed nine previous studies that focus on the application of STEM PBL in both special and inclusive educational settings. The findings suggest that STEM PBL is a successful and engaging pedagogical approach that positively influences various aspects of learning for students with disabilities. While the results highlight significant improvements in learning outcomes and student conduct during the educational process, several studies concurrently report challenges inherent in implementing STEM PBL for this demographic. Consequently, further research is warranted to explore how students with disabilities engage with a STEM PBL-focused curriculum. The implications of these findings are practical for educators, providing actionable insights to develop effective STEM PBL learning designs tailored for students with disabilities.